2016
DOI: 10.1371/journal.pone.0168229
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and Pro-Apoptotic Effects of MiR-4286 Inhibition in Melanoma Cells

Abstract: IntroductionMicroRNAs are essential regulators of gene expression at the post-transcriptional level. Their expression is altered in cancer tissues, and evaluation of these alterations is considered a promising tool used to diagnose and identify prognostic markers.Materials and methodsThe microRNA expression profiles of formalin-fixed, paraffin-embedded melanoma and melanocytic nevi samples were estimated with a microarray and subsequently validated by real-time PCR. Melanoma cells were transfected with miR-428… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 42 publications
2
33
0
1
Order By: Relevance
“…Our previous study found miR-155 to be the most notably upregulated and miR-205 the most notably downregulated microRNAs in melanoma, as compared with benign melanocytic tumours. 34 Those data are in accordance with several studies reporting the role of miR-155 as an oncogene and that of miR-205-5p as an oncosuppressor in various types of cancer. [35][36][37][38] Taken together, these findings prompted us to further investigate the target genes of miR-155 and miR-205.…”
Section: Discussionsupporting
confidence: 91%
“…Our previous study found miR-155 to be the most notably upregulated and miR-205 the most notably downregulated microRNAs in melanoma, as compared with benign melanocytic tumours. 34 Those data are in accordance with several studies reporting the role of miR-155 as an oncogene and that of miR-205-5p as an oncosuppressor in various types of cancer. [35][36][37][38] Taken together, these findings prompted us to further investigate the target genes of miR-155 and miR-205.…”
Section: Discussionsupporting
confidence: 91%
“…In our previous analysis of miRNA arrays, we found that miR‐4286 level was significantly increased in NSCLC tissues . It has been reported that miR‐4286 is a promising marker for diagnosing and identifying prognostic markers, including those in esophageal adenocarcinoma and melanoma, and inhibition of miR‐4286 represses cell proliferation . But the role of miR‐4286 in NSCLC remains unknown.…”
Section: Introductionmentioning
confidence: 93%
“…6 It has been reported that miR-4286 is a promising marker for diagnosing and identifying prognostic markers, including those in esophageal adenocarcinoma 7,8 and melanoma, 9 and inhibition of miR-4286 represses cell proliferation. 10 But the role of miR-4286 in NSCLC remains unknown. In current study, we firstly report that miR-4286 is overexpressed in NSCLC tissues and cell lines and exerts important functions in cell proliferation, migration, and invasion of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Komina et al () demonstrated that the application of a miR‐4286 inhibitor to melanoma cells resulted in a 2.6‐fold increase in the apoptosis rate and a 1.7‐fold decrease in cell proliferation, suggesting that this miRNA plays a role in protecting melanoma cells from apoptosis and promoting proliferation (Komina, Palkina, Aksenenko, Tsyrenzhapova, & Ruksha, ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Hanna et al (2012) showed that decreased levels of miR-205 correlated with worse outcomes, independent of stage, age, gender, and Breslow depth (Hanna, Hahn, Agarwal, & Rimm, 2012). Komina et al (2016) demonstrated that the application of a miR-4286 inhibitor to melanoma cells resulted in a 2.6-fold increase in the apoptosis rate and a 1.7-fold decrease in cell proliferation, suggesting that this miRNA plays a role in protecting melanoma cells from apoptosis and promoting proliferation (Komina, Palkina, Aksenenko, Tsyrenzhapova, & Ruksha, 2016).…”
Section: The Role Of Mirnas In Apoptosismentioning
confidence: 99%